Peritoneal Dialysis for Patients with Autosomal Dominant Polycystic Kidney Disease. Issue 4 (July 2017) - Khan, Sana; Giuliani, Anna; Crepaldi, Carlo; Ronco, Claudio; Rosner, Mitchell H.
End-stage renal disease secondary to autosomal dominant poly-cystic kidney (ADPKD) is a common issue worldwide. Peritoneal dialysis (PD) is a reasonable option for renal replacement therapy for these patients and should not be withheld due to concerns that the patient may not tolerate the fluid volumes in the peritoneal cavity. This review covers the existing data on the outcomes and complications associated with the use of PD in the polycystic kidney disease patient. In general, PD is well tolerated and outcomes in ADPKD patients are equivalent to or better than other patient groups.